Hardness of Ductile Cast Iron Castings and its Control in Praxis - Vasková, Iveta; Šebek, Peter; Mulik, Igor (Manufacturing Technology Journal, 2013)
Foundry is one of the oldest industry branch. In the evolution of humankind it played great role wih always improving mechanical properties of metals and in using of newest knowledges, it still plays one of the key function in all spheres of our lives. We meet everyday with the castings. It is the same if we sit in the car or we are eating the waffle. The production of every single casting needs individual approach for repeatidly achievement of desired material properties. Hardness is one of the basic property of metal materials in common. From hardness depends how easy, or how hard would be given material machined and what kind of materials, tools and machines would we need. In todays world of planning it is a matter of course to demand the same hardness for given material, so that the same machinability could be ensured and costs and machining time were minimalized. It is not always easy to assure this condition in praxis.
Keywords: ductile cast iron; hardness of castings; machinability; statistics